PERUBAHAN PILIHAN DALAM MENGAKSES TAYANGAN MEDIA INFORMASI DARI MEDIA STREAMING KE MEDIA DIGITAL - Oka Prayuda Barsan; Hendra Alfani; Septiana Wuladari (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2021)
In the rapid development of technology, new media, which are digital media for the public to access information, the emergence of digital media has left the mainstream media behind and made people make changes in the choice from mainstram media to digital media. Divusion theory of innovation that discusses the development of technology adopted by the community and continues to innovate in its development and Denis McQuail's theory that discusses new media, these two theories are considered to be sustainable with this research. The qualitative descriptive method by means of in-depth interviews is used as a research method to obtain valid data (valid). From the results of this study explains that the lunggaian villagers have changed their choices in accessing information from the mainstream media to digital media which are considered easier and more practical for access and lagging behind the mainstream media. From the results of this study it can be concluded that the development of media ranging from radio newspapers, television to digital media at this time the people of Lunggaian Village Lubuk Batang District also participated in the development even though in rural areas they use media ranging from radio, black and white tv then color tv to currently with online-based digital media that is getged.